THE EXISTENCE OF PANCASILA IN RESOLVING CONFLICTS OF DIFFERING VIEWS ON RELIGIOUS RIGHTS IN INDONESIA - Herlindah Herlindah; Indah Dwi Qurbani; Dorra Prisilia (Fakultas Hukum, Universitas Diponegoro, 2022)
This research investigates how Pancasila (the Five Principles) could serve as an equilibrium in regulating the freedom of religion in Indonesia and how these five principles could negotiate the concept of this freedom within the coverage of national Human Rights affected by western human rights related to the concept of the freedom of religions within the scope of Islam. The three different regulatory concepts regarding freedom of religion in Indonesia, constituting Islamic law, International Human Rights, and Particular Human Rights, have always sparked conflict unless these three concepts are accommodated by law. The analysis was performed by employing the doctrine of margin of appreciation. This research reveals that Pancasila could serve as the fundamental of Indonesia in facilitating the freedom of religion. This research also employed a normative-juridical method, interdisciplinary, statutory, and conceptual approaches.